æ¨¡ä»¿æ•™å¦æ³•å¯¹BINA UTAMAåˆä¸ä¸€å¹´çº§å¦ç”ŸæŽŒæ¡æ±‰è¯å£°æ¯èƒ½åŠ›çš„å½±å“ - Damayanti, Aditya; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCurrently in Indonesia, especially in Pontianak , many people start to learn Mandarin, because they think that Mandarin is one of the most important subjects. But students who have never learned Mandarin, they assume that Mandarin is a very difficult language to learn. They feel that every aspect in Mandarin like consonants, vowels and tones is very difficult for them to distinguish and pronounce, because they are still influenced by their mother tongue.From this case, the authors conducted a research with imitation methods to determine the effect of imitation methods in teaching consonants to 7A grade students of SMP BinaUtama. This research used a test method to determine changes in students 'abilities before and after teaching. The results of research was imitation method can improve students' ability to master Mandarin consonants. Keywords: imitation method ,the consonant, test method